Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1186/s13071-016-1418-4
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of recombinant multi-epitope proteins for diagnosis of goat schistosomiasis by enzyme-linked immunosorbent assay

Abstract: BackgroundSchistosomiasis is a huge threat to human and animal health. Apart from bovines, goats play an important role in the transmission of schistosomiasis in some endemic areas of China. An accessible, quality-assured goat schistosomiasis diagnostic technique is needed. Recently, our laboratory identified two recombinant diagnostic antigens, SjPGM and SjRAD23 via an immuno-proteomic method. The application of these two recombinant antigens to develop a higher sensitivity and specificity technique for the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 31 publications
0
23
0
Order By: Relevance
“…Antibody detection has been shown to be more sensitive than traditional parasitological microscopic techniques. It is needed in areas characterized by a low level of transmission, low prevalence, and particularly low intensity [20,21]. ESPs are released into the blood circulation and may induce the production of antibodies by infected hosts [22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Antibody detection has been shown to be more sensitive than traditional parasitological microscopic techniques. It is needed in areas characterized by a low level of transmission, low prevalence, and particularly low intensity [20,21]. ESPs are released into the blood circulation and may induce the production of antibodies by infected hosts [22].…”
Section: Discussionmentioning
confidence: 99%
“…Then, the animals were experimentally infected with 8000 H. contortus L3. Serum samples were collected from each goat before infection (negative control) and at 7,14,21,35,49,63,85, and 103 DPI.…”
Section: Expression and Purification Of Rhcadrmmentioning
confidence: 99%
“…In this study, indirect ELISA was performed to evaluate the potential serodiagnostic role of rHcRas protein during the prepatent period. Previously, it was reported that the antibody detection method was more sensitive than microscopic parasitological techniques and could be used in areas characterized by a low level of transmission, prevalence, and intensity [26,27]. The Western blotting analysis of this study showed that the rHcRas antigen was first detected at 14 DPI and persisted until 103 DPI.…”
Section: Discussionmentioning
confidence: 55%
“…Hence, antibody detection has been proved to be more sensitive than traditional parasitological microscopic techniques during early stage of infection. It is needed in areas characterized by a low level of transmission, low prevalence and particular low intensity [40].…”
Section: Discussionmentioning
confidence: 99%